2011
DOI: 10.1371/journal.pgen.1001359
|View full text |Cite
|
Sign up to set email alerts
|

The Recombinases Rad51 and Dmc1 Play Distinct Roles in DNA Break Repair and Recombination Partner Choice in the Meiosis of Tetrahymena

Abstract: Repair of programmed DNA double-strand breaks (DSBs) by meiotic recombination relies on the generation of flanking 3′ single-stranded DNA overhangs and their interaction with a homologous double-stranded DNA template. In various common model organisms, the ubiquitous strand exchange protein Rad51 and its meiosis-specific homologue Dmc1 have been implicated in the joint promotion of DNA–strand exchange at meiotic recombination sites. However, the division of labor between these two recombinases is still a puzzl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 58 publications
5
97
0
Order By: Relevance
“…The number of Dmc1p foci in non-elongated nuclei (179618 s.d., n510) at t53.5 h after meiotic induction was similar to the number of foci in elongated nuclei of the control (170632 s.d., n514) (Fig. 4A) (for the method of counting foci, see Howard-Till et al, 2011). This indicates that DSBs are efficiently induced when no bouquet is formed.…”
Section: Dsbs Are Repaired Even When Bouquet Formation Is Preventedmentioning
confidence: 90%
See 2 more Smart Citations
“…The number of Dmc1p foci in non-elongated nuclei (179618 s.d., n510) at t53.5 h after meiotic induction was similar to the number of foci in elongated nuclei of the control (170632 s.d., n514) (Fig. 4A) (for the method of counting foci, see Howard-Till et al, 2011). This indicates that DSBs are efficiently induced when no bouquet is formed.…”
Section: Dsbs Are Repaired Even When Bouquet Formation Is Preventedmentioning
confidence: 90%
“…The meiotic nuclei will first become drop-shaped, then spindle-shaped, before elongation culminates in the so-called crescent. During elongation, DSBs are formed, recombination protein Dmc1 forms foci on chromatin, and homologous chromosomes become juxtaposed (Loidl and Mochizuki, 2009;Lukaszewicz et al, 2010;Howard-Till et al, 2011). Later, nuclei shorten and chromatin condenses into threads.…”
Section: Depletion Of Centromeric Protein Cna1 Prevents Centromere CLmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data indicate that DMC1 abundance at DSB sites is negatively regulated by the ATR kinase and that the strand-exchange activity of RAD51 may be dispensable for meiosis. Nevertheless, in all organisms analyzed, RAD51 is an essential meiotic repair protein (Shinohara et al, 1992;Rinaldo et al, 2002;Li et al, 2004;Howard-Till et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…30 Dmc1 then binds to the 3 0 ends of these DNA molecules and the Hop2-Mnd1 complex stabilizes Dmc1-ssDNA binding to promote homology search DNA strand invasion, an important stage in DSB repair. 24,32 Analysis of fold changes in gene expression between cdk3D and WT showed that genes related to DSB repair were down-regulated in cdk3D cells (Fig. 3B).…”
Section: Cdk3 Acts Upstream Of Dsb Formation In T Thermophilamentioning
confidence: 99%